Covid 19: impactos na oportunidade de participação em lazer de crianças com paralisia cerebral - Bagatini, Beatriz (Universidade Federal de São Carlos, 2021)
In 2020, the World Health Organization declared that there was a pandemic due to the SARS-COV-2 virus, which caused social isolation, restricting people's access to community environments. In view of this, the importance of understanding the changes in leisure and routine activities of children with cerebral palsy was seen, since they were not attending school in person. That said, the present study aims to compare the leisure activities of children with cerebral palsy before and during the period of social isolation, through specific objectives: a) map the leisure activities of children with cerebral palsy before and after the pandemic by Covid-19; b) to identify the participation of children with cerebral palsy in leisure activities; c) to identify possible changes in the routine of children with cerebral palsy caused by social isolation. For this, three mothers / guardians of children with cerebral palsy, aged 33 to 70 years, who had already been involved in a study conducted in 2018, participated in the study, which answered an interview, the PEM-CY questionnaire, and the PEDI. Except for PEDI, all instruments were reapplied in 2020, with adaptations, and a socioeconomic questionnaire was added. The method is characterized as longitudinal descriptive, and the data of the interviews were analyzed from the thematic analysis of the content and the questionnaires followed their own instructions. Two initial classifications were obtained from the interviews, resulting in 13 nuclei of meaning until reaching 14 themes to be presented and discussed. The results indicated that children with cerebral palsy had changes in leisure participation, and routine activities due to the covid-19 pandemic. Community activities were impaired, in home activities, there was no difference before and during social isolation, however, children spend more time at home and miss the school and the fun that the space offers. The pandemic also led to changes in routine, changes in mood and family life. Thus, the study concluded that the covid-19 pandemic had an impact on the leisure activities of children with cerebral palsy also on other aspects of their daily life. It was concluded that the impacts of social isolation were significant for the children in the study, which requires attention in view of the opportunities in the leisure area that children with CP have compared to children with typical development.
Covid 19: impacts on the opportunity of participation in leisure of children with cerebral palsy
Covid 19: impactos en la oportunidad de participación en el tiempo libre de niños con parálisis cerebral
Keywords: Educação Especial; Isolamento social; Lazer; Paralisia cerebral; COVID-19; Special Education; Social isolation; Leisure; Cerebral palsy; CIENCIAS HUMANAS::EDUCACAO